2015
DOI: 10.1111/ajt.13271
|View full text |Cite
|
Sign up to set email alerts
|

Microvesicles Derived From Human Mesenchymal Stem Cells Restore Alveolar Fluid Clearance in Human Lungs Rejected for Transplantation

Abstract: The need to increase the donor pool for lung transplantation is a major public health issue. We previously found that administration of mesenchymal stem cells “rehabilitated” marginal donor lungs rejected for transplantation using ex vivo lung perfusion. However, the use of stem cells has some inherent limitation such as the potential for tumor formation. In the current study, we hypothesized that microvesicles, small anuclear membrane fragments constitutively released from mesenchymal stem cells, may be a goo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
125
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(137 citation statements)
references
References 36 publications
(58 reference statements)
4
125
0
1
Order By: Relevance
“…Litvack and colleagues also showed that, although not true AMs, stem cell-derived, alveolar-like macrophages improved bacterial and neutrophil clearance in another model of lung injury (49), but further study is required to determine the safety and feasibility of these treatment modalities. Moreover, these data contribute to the growing body of literature that suggests the potential of MSC-derived EVs as a therapy in place of MSCs (25)(26)(27). Although there have been no reports of MSC-induced neoplasia to date, EVs cannot themselves transform to form tumors, reducing the potential risk associated with cell-based therapy.…”
Section: Original Articlementioning
confidence: 65%
See 2 more Smart Citations
“…Litvack and colleagues also showed that, although not true AMs, stem cell-derived, alveolar-like macrophages improved bacterial and neutrophil clearance in another model of lung injury (49), but further study is required to determine the safety and feasibility of these treatment modalities. Moreover, these data contribute to the growing body of literature that suggests the potential of MSC-derived EVs as a therapy in place of MSCs (25)(26)(27). Although there have been no reports of MSC-induced neoplasia to date, EVs cannot themselves transform to form tumors, reducing the potential risk associated with cell-based therapy.…”
Section: Original Articlementioning
confidence: 65%
“…Additionally, the capacity of MSCs to induce polarization toward M2-type monocytes/macrophages, identified by CD206 expression, may serve as a biomarker for MSC efficacy in clinical samples. EVs have emerged as a major contributor to the therapeutic effects of MSCs in lung injury, capable of recapitulating many of the effects of the whole-cell therapy (25)(26)(27). CD44 expression on MSC-derived EVs was shown to be necessary for their uptake and therapeutic effect on target cells (27,50).…”
Section: Msc-derived Ev-treated Murine Amsmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, only a few groups have studied the therapeutic effects of MSC vesicles in acute inflammatory lung diseases such as ALI[16, 103105], pulmonary artery hypertension (PAH)[106, 107] and asthma[108]. Although the mechanisms of action have not been fully defined, these groups have demonstrated that MSC vesicles are as potent as their parent stem cells as therapy (Figure 4).…”
Section: Mesenchymal Stem Cells Extracellular Vesicles For Acute Lmentioning
confidence: 99%
“…In an ex vivo human lung perfusion model of I/R seen in lung transplantation[15], Gennai et al[105] found that MSC MVs increased alveolar fluid clearance (e.g., ability to absorb pulmonary edema fluid) in a dose-dependent manner, decreased lung weight gain following perfusion and ventilation, and improved airway and hemodynamic parameters compared to perfusion alone. Co-administration of MVs with anti-CD44 antibody attenuated these effects, suggesting a key role of the CD44 receptor in the internalization of the MVs into the injured host cell and its effect.…”
Section: Mesenchymal Stem Cells Extracellular Vesicles For Acute Lmentioning
confidence: 99%